Composition and fungitoxicity of essential oil of citronella grass as affected by organic fertilization - Veloso, Ronice Alves; Castro, Henrique Guilhon de; Cardoso, Dione Pereira; Santos, Gil Rodrigues dos; Barbosa, Luiz Cláudio de Almeida; Silva, Kamilla Pires da (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate the influence of organic fertilization on the content and composition of the essential oil of citronella grass (Cymbopogon nardus), as well as to assess the fungitoxicity of this oil to the mycelial growth of the fungi Didymella bryoniae, Colletotrichum gloeosporioides, and Amphobotrys ricini. The extraction of the essential oil was done by hydrodistillation in plants cultivated with four doses of organic fertilizer (0, 3, 6, and 9 kg matured cattle manure per hole), and the identification of the chemical compounds was done by gas chromatography/mass spectroscopy. To evaluate the inhibition of mycelial growth, the experiment was installed in a completely randomized design in a factorial arrangement. Seven aliquots of essential oil were tested (0, 5, 10, 15, 20, 25, and 30 μL) in five evaluating times, with four replicates. The contents of the essencial oil in citronella grass were note affected by organic fertilization, and the oil includes 24 chemical compounds, among these monoterpenes and sesquiterpenes, with higher concentrations of the compounds citronellal, β‑citronellol, geraniol, and elemol. The essential oil of citronella grass has higher inhibition effect on Amphobotrys ricini, when compared to the fungi Didymella bryoniae e Colletotrichum gloeosporioides.